APLIKASI TANGGAP DARURAT MASYARAKAT DI KECAMATAN TELANAIPURA KOTA JAMBI: Service, Emergency Response, Community, MYSQL, PHP, Web - Lisdarti, Lisdarti; Davidtra, Riki (LP2M Universitas Nurdin Hamzah, 2021)
In improving services regarding emergency response to the community, it is necessary to build a Community Emergency response application that can assist the Telanaipura sub-district, Jambi city in obtaining information on emergency reports or complaints from the community, in order to help speed up and simplify the emergency response process. Telanaipura sub-district office, Jambi city, which is located at Jl. Piere tended to RT. 12 Ex. Telanaipura Kec. Telanaipura Jambi City. The purpose of this research is to create a Mobile-Based Community Emergency Response Application in Telanaipura District, Jambi City. Making this application is done by means of data collection, system planning, system analysis, system and database design. Making application programs developed with PHP. The database used is MySQL. The input needs of the application program are user data, community data, complaint data, category data, contact data and news data. Process requirements needed are: login process, master data process, complaint process and report process. Expenditure data generated is in the form of information that will be displayed, among others: complaint data information, community data information, complaint status data information, contact data information and news data information. With the existence of a new system that has been designed and created by researchers, it can help facilitate the parties involved in improving emergency response services to the community